Critical Insights into Gig Economy: A Peninsular Malaysia Case Study - Abdullah, Nurhidayah; Ismail, Maria Mohd; Murad, Muhammad Syariqul Huzni; Jusoff, Kamaruzaman; Kurniawan, Faizal; Salah, Mohammed (Journal of Ecohumanism, 2024)
The rise of the gig workers has transformed the employment landscape, presenting both opportunities and challenges for workers globally. It has disrupted the traditional meaning of ‘employee’ with ambiguous and complex aspects, especially gig workers’ status. Practically, gig workers are individuals working under a contract for service with flexibility and independence elements that give them a sense of autonomy in performing their work. This study delves into the specific case of Peninsular Malay- sia, investigating the issues and challenges gig workers face in the thriving market. The research adopts both library research and qualitative research methods, including interviews using a semi-structured approach. A total of 10 respondents were interviewed using a semi-structured method. The findings revealed that the challenges dwell in the issues of gig workers, which require high-time intervention of governance, policies, and legisla- tion; there is still no definition of gig workers. There is a lack of social protection, an absence of employment contracts, an absence of price regu- latory control, poor operational services, a gap between platform owners and the government, and a piecemeal institutional framework. Hence, this study offered recommendations on how to improve the enforcement.